PENGEMBANGAN BAHAN AJAR E-MODUL PADA PELAJARAN TIK KELAS VII SMPN 1 KAUMAN - Nurna listya purnamasari (Program Studi Teknologi Informasi, Universitas Muhammadiyah Muara Bungo, 2020)
Teaching material is something that has a significant role in teaching and learning activities. Not only relying on teachers as a source, teaching materials can influence the course of teaching and learning activities. Teaching materials can be grouped into four categories, namely printed teaching materials, listening teaching materials, listening view teaching materials, interactive multimedia teaching materials. In this study, teaching materials in the form of a Lectora-based e-module were carried out on class VII students of SMPN 1 Kauman Tulungagung, with the following test results: the media expert's assessment resulted in a feasibility percentage of 82.8%, while the results of the assessment from material experts were obtained. the result of the percentage of feasibility is 92.5%.